The use of pumping station in conjunction with Kuching barrage for flood mitigation - Mohamad, N. (Universiti Malaysia Sarawak, UNIMAS, 2009)
Kuching Barrage is one of the existing flood mitigation measures which built to prevent the flooding problem in the Sarawak River. Even though there is a Kuching Barrage, but the flooding problems still occurs especially in Kuching area. External floods are caused by high flood water and high tides from Sarawak River. The most critical condition arises when both king tides and flood water from upper tributaries reach a place at the same time. This research discusses the use of pumping station by presenting the flooding scenarios without and with pumping system using InfoWorks River Simulation (RS). Data, Geographical Information System (GIS) preparations and details on modeling approach are presented. The Wallingford Software model is used to design the pumping station as a protection system to pump out or drains out the excess water during flood from Sarawak River into the sea when the Kuching Barrage gates were closed. The pumps would be set in motion during heavy rain and high tides which the pumps in the pumping station were modeled in parallel. The simulation of the modeling with pumping station had been carried out with many numbers of pumps until there was no serious flooding occurs in Sarawak River. The study had been carried out at the cross section S46 (Kuala Maong) which the flood stage hydrograph and cross section profile had been generated by Infowork RS in order to show the results of a propagation of flood water profiles. Kuala Maong area had been selected due to its known frequent flooding problems. The results from the hydraulic model showed that the pumping station is capable of reducing flood.